EXPLORING INTERPERSONAL INTERACTION IN WRITTEN DISCOURSE - Risdaneva Risdaneva (Englisia: Journal of Language, Education, and Humanities, 2014)
The purpose of any discourses, either spoken or written ones, is to communicate the messages to the targeted audiences. Written discourse appears to be the most cau-tious piece of work since it is a product of a well-organised and long-term writing process. To achieve the communicative purpose, an author should interpersonally interact with the targeted readers. The interpersonal interaction can be realised through the use of modalisation to express certainty and uncertainty as well as the use of attitudinal evaluation to evaluate things, events, people, situations and etc. In this case, the analysis of some extracts which are produced as guidelines for the teachers suggest that the written texts are quite convincing and evaluative as well as successful in persuading the readers. This is typical to this genre of discourse as its ultimate goal is to win over the interest of the reader in using the product. In other word, the author tries to make the text convincing and persuasive in order to win over the teachers’ interest in using the textbook in their classrooms.